OPEN-SOURCE SOFTWARE LIFECYCLE CLASSIFICATION: MEASUREMENT OF THE END-OF-LIFE (EoL) SOFTWARE - Дем’янчук, Сергій; Мартиненко, Роман; Лопухович, Володимир (SWorldJournal, 2025)
The exponential growth of the open-source software (OSS) ecosystem, characterized by increasing corporate-communal engagement patterns, has created unprecedented challenges in managing software lifecycles, particularly in identifying and assessing end-of-